ANALISIS ANGGARAN PROYEK SEBAGAI ALAT PENGENDALIAN BIAYA PADA PT MOAINDO PRIMA DI PAKET PEKERJAAN LANJUTAN PEMBANGUNAN JARINGAN IRIGASI D.I. RAPAK OROS KABUPATEN KUTAI BARAT PROVINSI KALIMANTAN TIMUR - Daury Rahadian Sriandanda, Mega Indah Nur Azizah1 Eka Yudhyani 2 (EKONOMIA, 2021)
The purpose of this research is to know and analyze the project budget as a cost control tool at PT Moaindo Prima in the advanced package of work on the construction of the D.I Rapak Oros irrigation network, West Kutai district, East Kalimantan province. In accordance with the objectives of this study, Â the subject matter put forward â€œIs the project budget as a cost control tool at PT Moaindo Prima a further package for the construction work of the D.I Rapak Oros irrigation network, West Kutai Regency, East Kalimantan province in accordance with the realization of the costs?â€The basic theory used in this study is cost accounting which focuses on the budget and the realization of the project costs of PT Moaindo Prima. The data collection technique was carried out by means of field research and library research. The data used to determine and analyze the suitability between the budget for the project of the D.I. Irrigation Network Development project. Rapak Oros, West Kutai Regency, East Kalimantan Province with the realization of the cost. The analytical tool use analysis of variance.The result of this research is that the hypothesis is accepted because there is a mismatch in the project cost budget as a cost control tool at PT Moaindo Prima in the Advanced Work Package for the Development of Irrigation Network D.I. Rapak Oros, West Kutai Regency, East Kalimantan Proviance with the realization of the costs.Â